2021
DOI: 10.1242/dev.199894
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis mediated by an atypical CUBAM complex modulates slit diaphragm dynamics in nephrocytes

Abstract: The vertebrate endocytic receptor CUBAM, consisting of three cubilin monomers complexed with a single amnionless molecule, plays a major role in protein reabsorption in the renal proximal tubule. Here, we show that Drosophila CUBAM is a tripartite complex composed of Amnionless and two cubilin paralogues, Cubilin and Cubilin2, and that it is required for nephrocyte slit diaphragm (SD) dynamics. Loss of CUBAM-mediated endocytosis induces dramatic morphological changes in nephrocytes and promotes enlarged ingres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…In this experimental setup, excessive uptake manifests in an increase in these parameters compared with control cells ( Figure 1, J and N and Supplemental Figure S1, A and P), as seen in the case of Rab5 overexpression, a known enhancer of endocytic activity ( Bucci et al. , 1992 ; Atienza-Manuel et al. , 2021 ) that we used as a positive control ( Figure 1, K and N and Supplemental Figure S1, B and P).…”
Section: Resultsmentioning
confidence: 82%
“…In this experimental setup, excessive uptake manifests in an increase in these parameters compared with control cells ( Figure 1, J and N and Supplemental Figure S1, A and P), as seen in the case of Rab5 overexpression, a known enhancer of endocytic activity ( Bucci et al. , 1992 ; Atienza-Manuel et al. , 2021 ) that we used as a positive control ( Figure 1, K and N and Supplemental Figure S1, B and P).…”
Section: Resultsmentioning
confidence: 82%
“… 13 , 14 The Cubn-Amn complex mediates protein uptake in renal proximal tubule cells, and is also critical to nephrocyte function. 38 , 39 , 40 It has been noted that the labyrinthine channels of fly nephrocytes, with their high levels of endocytosis and proximity to the slit diaphragm filtration barrier, bear functional similarity to proximal tubule cells of the vertebrate nephron. 40 …”
Section: Resultsmentioning
confidence: 99%
“…This finding suggests nephrocytes are not only a model for podocyte biology, but also for proximal tubular cells. However, in recent studies cubilin and amnionless have been identified to be expressed in mammalian podocytes and to be important for nephrocyte diaphragm remodelling in nephrocytes ( Prabakaran et al, 2012 ; Gianesello et al, 2017 ; Atienza-Manuel et al, 2021 ). Moreover, according to single nucleus RNA-seq in adult fly kidneys, nephrocytes do not show an overlap with murine proximal tubular cells, but with podocytes and parietal epithelium ( Xu et al, 2021 Preprint ).…”
Section: Discussionmentioning
confidence: 99%